Histological study of endoscopic biopsies from the lower gastrointestinal tract (Journal of Pathology of Nepal, 2022)
Background: Endoscopy of the gastrointestinal tract is seen as an essential diagnostic tool because it can provide an in-depth visual assessment of gastrointestinal mucosa and allows for tissue sampling. This study aims to find out the histological diagnosis of various tissues biopsied from the lower GIT endoscopically.Materials and methods: It is a retrospective observational study conducted in the Department of Pathology, Fewa City Hospital and Research Center, Pokhara, Nepal from March 2021 to February 2022.Results: Total number of samples taken into the study was 174. Nonspecific inflammation was the commonest lesion in ileal, colon, and rectal biopsies.Conclusions: Lower GI tract is targeted to a wide range of diseases, ranging from inflammatory to malignant entities. Endoscopy and biopsy for suspected lesions is a trusted approach for investigating and managing GI tract pathologies.